A History of Nonviolence: Insecurity and the Normative Power of the Imagined in Costa Rica - Sebastian Huhn (German Institute of Global and Area Studies (GIGA), 2008)
Crime, violence, and insecurity are among the most important social topics in contemporary Costa Rica. These three issues play a central role in the media, politics, and everyday life, and the impression has emerged that security has changed for the worse and that society is now threatened permanently. However, crime statistics do not support this perception. The paper thus asks why violence and crime generate such huge fear in society. The thesis is that the Costa Rican national identity - with Costa Rica constructed as a nonviolent nation - impedes a realistic discussion about the phenomena and their causes, and simultaneously provides a platform for sensationalism and the social construction of fear. – – Die Angst vor Gewalt, Kriminalität und Unsicherheit ist in Costa Rica eines der wichtigsten gesellschaftlichen Probleme. In den Medien, der Politik und dem Alltag nehmen Gewalt und Kriminalität großen Raum ein und es entsteht der Eindruck, die Sicherheitslage habe sich dramatisch verschlechtert und die Bevölkerung müsse in ständiger Angst leben. Auf der Grundlage, dass Kriminalitätsstatistiken diese gesamtgesellschaftliche Angst nicht rechtfertigen, geht dieser Beitrag der Frage nach, warum Gewalt und Kriminalität heute ausgerechnet in Costa Rica so große Angst und Unsicherheit erzeugen. Die These lautet, dass die costaricanische nationale Identität und die 'nationale Erzählung' - in der Costa Rica als gewaltfreie Nation gedacht wird - einerseits den Blick auf die Ursachen von Gewalt und Kriminalität versperren und andererseits die Projektionsfläche für die soziale Konstruktion gesellschaftlicher Angst darstellen.
Keywords: 300; Costa Rica; violence; crime; national identity; public discourse